C-field cosmological models: revisited. (December 2016) - Yadav, Anil Kumar; Ali, Ahmad Tawfiq; Ray, Saibal; Rahaman, Farook; Sardar, Iftikar Hossain
Abstract: We investigate plane symmetric spacetime filled with perfect fluid in the C -field cosmology of Hoyle and Narlikar. A new class of exact solutions has been obtained by considering the creation field C as a function of time only. To get the deterministic solution, it has been assumed that the rate of creation of matter-energy density is proportional to the strength of the existing C -field energy density. Several physical aspects and geometrical properties of the models are discussed in detail, especially showing that some of our solutions of C -field cosmology are free from singularity in contrast to the Big Bang cosmology. A comparative study has been carried out between two models, one singular and the other nonsingular, by contrasting the behaviour of the physical parameters. We note that the model in a unique way represents both the features of the accelerating as well as decelerating universe depending on the parameters and thus seems to provide glimpses of the oscillating or cyclic model of the universe without invoking any other agent or theory in allowing cyclicity.